Potential fMRI correlates of 40-Hz phase locking in primary auditory cortex, thalamus and midbrain - Steinmann, Iris; Gutschalk, Alexander (NeuroImage, 2011)
MEG and BOLD fMRI are both related to post-synaptic activity, but not all components of the MEG appear to be equally reflected by the BOLD response. To evaluate potential BOLD correlates of the auditory 40-Hz steady-state response (SSR), 40-Hz amplitude-modulated (AM) tones and pure-tones with 1000-Hz tone frequency and 32-s tone duration were presented to 12 listeners in fMRI and MEG. The SSR evoked by AM-tones is readily separated from the onset, offset and sustained fields in MEG by a high-pass filter. For fMRI, a contrast of AM- versus pure-tones was used to estimate activity related more specifically to the 40-Hz SSR, but excluding other activity that is evoked by AM and pure-tones alike. This contrast showed sustained BOLD activation confined to the medial part of Heschl's gyrus, the location of the primary auditory cortex, as well as activity in the medial geniculate body (MGB) and the inferior colliculus (IC). Transient BOLD onset and offset responses were prominent throughout the auditory cortex. In contrast, sustained BOLD activity for pure-tones was weak and did not match well with the time course of the sustained field, suggesting that there is no reliable BOLD correlate of the sustained field in MEG. The sustained BOLD activity in primary auditory cortex is therefore more likely linked to the phase-locked SSR. Enhanced BOLD for AM compared to pure-tones in the IC and MGB may similarly be related to phase locking.
Online verfügbar 3 August 2010
Gesehen am 21.10.2022